THE RISK OF TRANSMISSION OF COVID-19, COMMUNITY STIGMA, THE AVAILABILITY OF PPE AS A STRESS TRIGGER FOR HEALTH WORKERS - Arif Fatah Hidayat; Sri Iswati (Airlangga Development Journal, 2023)
In the midst of the Covid-19 pandemic, the role of health workers is very important. The high risk of transmission causes stress for them. The aim of the research is to empirically determine the influence of the risk of Covid-19 transmission, public stigma, and the availability of PPE on the stress of health workers in hospitals. Using a quantitative approach, the cross section with a sample of 122 was tested with multinomial logistic regressions. Univariate results show that the risk of transmission is low, public stigma is moderate, PPE availability is high and stress is moderate. The results of the bivariate analysis show that the risk of Covid-19 transmission has a positive effect, community stigma has a positive effect, and the availability of PPE has a positive effect on health worker stress, all of which are significant. Multivariate analysis results indicate that all independent variables have a significant effect on health worker stress. The risk variable for transmitting Covid-19 is the most dominant. Screening for the risk of Covid-19 transmission, complete personal protective equipment, and positive stigma can provide health workers with a sense of security so that the risk of stress can be minimized.